Engineering companies and their readiness for Industry 4.0. Issue 5 (5th April 2021) - Váně, Jan; Kalvas, František; Basl, Josef
Abstract : Purpose: This case study of the readiness of engineering companies for Industry 4.0 (I4.0) presents how surveyed key figures manage the implementation of I4.0. The research comprised a census of larger and medium-sized engineering companies in the Pilsen region of the Czech Republic. The selected region is characterised by a long industrial tradition and a high concentration of technical and technology-oriented companies. The survey questionnaire monitors a wide range of topics. In this text, the authors present the results only from selected areas. In particular, the authors examined: (1) the use of I4.0 technologies in individual areas, (2) the level of the digital strategy (DS), (3) factors influencing investments in I4.0 technologies, (4) the impact of I4.0 on the workforce and (5) existing threats to I4.0 implementation. The purpose of this paper is to show how key figures with a real impact on the implementation of I4.0 think and act in practice (as opposed to declarations). Design/methodology/approach: In the presented article, thanks to the unique data obtained in the form of a census in the selected, traditionally engineering-oriented Pilsen region, and within the highly industrially oriented Czech Republic, the authors explored the state of readiness of companies for implementation of I4.0. The obtained data allowed the authors to present, in a suitably descriptive way, the current level, with respect to the future, of the planned use of I4.0 principles in the surveyed companies. They monitored not only the state of the adoption process (Industry of 4.0 technologies) compared to the declared proclamations but also which phenomena represent key obstacles. Findings: First, medium-sized companies have barely implemented I4.0, whereas I4.0 is more often implemented in larger companies, especially the so-called DS aspect of I4.0. Furthermore, it appears that larger companies also clearly consider I4.0 more often and see it more significantly as a key success factor. Second, the survey highlighted the fact that customer satisfaction is the determining impetus for the introduction of I4.0. It can be assumed that with an increase in pressure from customers and a decrease in the price of technology, the introduction of I4.0 will increase. The third important finding is that the authors can observe a kind of two-stage flow of innovation in the results. The transformation towards I4.0 is approached by larger companies first, because they are more sensitive to customer satisfaction, are looking for new opportunities, and have greater resources to cover the costly implementation of innovations. Originality/value: In the presented article, thanks to the unique data obtained in the form of a census in the selected, traditionally engineering-oriented Pilsen region, and within the highly industrially oriented Czech Republic, the authors explored the state of implementation of I4.0. The obtained data allowed the authors to present, in a suitably descriptive way, the current level, with respect to the future, of the planned use of I4.0 principles in the surveyed companies.